Nursing Based Paramedics’ Perception on Their Future Career Under the Health, Safety, and Environment: A Phenomenological Study - Nurhadi bin Amin; Isak Jurun Hans Tukayo; Syaifoel Hardy; Ridha Afzal (Jurnal Keperawatan, 2022)
A very common trend for nurses working in the industry in Indonesia is paramedics, where many nurses left the nursing profession and switched to health, safety, and environment (HSE). They perceived a better future career under the HSE. to explore the experience of nurses working as paramedics in industries in which they have a perception that the future of the Health, Safety and Environment (HSE) profession is better than nursing. The implication is to help provide insight into the prospects of nursing professionals scientifically and to straighten the better understanding about paramedic according to the existing laws.This study used a qualitative design with a descriptive phenomenological approach. The instrument used was a list of semi-structured interview with questions given to 13 participants by telephone or WhatsApp. The participants were Indonesian industrial nurses working as paramedics (10 nurses in Indonesia, 2 in Qatar, and 1 in Saudi Arabia). Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The stages include marking keywords and ideas in the data, identifying keywords, finding themes that come from the data, compiling a coding system, and then analyzing it.Five themes were found, namely (1) perceived that the benefits at HSE were better than nursing, (2) working under HSE has a more dynamic future career plan, (3) satisfied with HSE, (4) better access to education, (5) HSE work locations were more challenging. Their perception on HSE was evidenced by 100% participants perceived better benefits, better future career plan, satisfied with their work, education access, and work location. Three out of 13 could continue their education with a dual focus, HSE and nursing were both engaged in. Paramedic is perceived more profitable than nursing, while the nursing profession can promise the same thing.